2019
DOI: 10.1097/pcc.0000000000001881
|View full text |Cite
|
Sign up to set email alerts
|

Early Protocolized Versus Usual Care Rehabilitation for Pediatric Neurocritical Care Patients: A Randomized Controlled Trial

Abstract: TWEET Early, ICU-based and personalized physical, occupational, and speech and language therapy sessions were feasible and safe in pediatric neurocritical care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 50 publications
1
19
0
4
Order By: Relevance
“…Only 0.2% of all mobility events were associated with dislodgement of a device, comparable to the 0.6% rate in adults [20]. Therefore, our data, in parallel with evidence from single-centre PICU studies [21,22], suggest that mobilization of PICU patients is safe. There are several important similarities and differences with the USA-PARK-PICU findings [12], a retrospective Canadian multicentre PICU study [23], and adult point prevalence studies of ICU mobilization practices [18].…”
Section: Discussionsupporting
confidence: 74%
“…Only 0.2% of all mobility events were associated with dislodgement of a device, comparable to the 0.6% rate in adults [20]. Therefore, our data, in parallel with evidence from single-centre PICU studies [21,22], suggest that mobilization of PICU patients is safe. There are several important similarities and differences with the USA-PARK-PICU findings [12], a retrospective Canadian multicentre PICU study [23], and adult point prevalence studies of ICU mobilization practices [18].…”
Section: Discussionsupporting
confidence: 74%
“…This finding is consistent with prior literature suggesting that less than half of this population receive PICU rehabilitation services as a part of usual care [ 32 34 ]. Recent randomized control trials have found it feasible and safe to increase PICU-based rehabilitation services [ 35 , 36 ], and acute rehabilitation is the only intervention that has been identified thus far for improving physical function in critically ill patients [ 37 , 38 ]. Inclusion of rehabilitation services in the care of PICU patients allows for personalized strategic plans to be implemented for patients and families that can facilitate a smoother transition home and improve child and family outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…35 The results of this review suggest that levels of comfort with mobilization may be evolving with increasing safety and feasibility data in children and indirect evidence from the adult population. Cardiorespiratory instability 20,21 Mortality (no. of deaths recorded) 1220 (9 observational studies) ⊕○○○ Very low †, ‡, § Across 9 studies, 4 deaths were reported among 494 children receiving mobilization (0.8%) vs 27 of 720 (3.75%) in control group.…”
Section: Discussionmentioning
confidence: 99%
“…23,26 Four studies used interactive videogames and/ or in-bed cycling to facilitate mobilization. 3,22-24 "Early" mobilization was defined as within 48 hours of PICU admission in 3 studies 21,29,30 and 72 hours of PICU admission in another. 26 The wEECYCLE pilot RCT evaluated early mobilization practice guidelines as their standard of care, which recommended screening for appropriateness within 24 hours of PICU admission, and defined early as when contraindications are absent and a set of systems-based safety criteria are met.…”
Section: Mobility Interventions Timing and Definitions Of "Early"mentioning
confidence: 99%